Mimetic Lives - Kitzinger, Chloë (Northwestern University Press, 2022)
What makes some characters seem so real? Mimetic Lives explores this unprecedented question on the rich ground of Tolstoy’s and Dostoevsky’s fiction. Each author discovered techniques for intensifying the aesthetic illusion Kitzinger calls mimetic life: the reader’s sense of a character’s embodied existence. Both authors tested the limits of that illusion by pushing it toward the novel’s formal and generic bounds. Through new readings of War and Peace, Anna Karenina, The Brothers Karamazov, and other novels, Kitzinger traces the productive tension between these impulses. She shows how these lifelike characters are made, and why the authors’ dreams of carrying the illusion of life beyond the novel fail. Kitzinger challenges the contemporary truism that novels educate by providing models for the perspectives of others. The realist novel’s power to create compelling fictional persons underscores its resources as a form for thought, and its limits as a source of change.